Understanding Shirk in The Qur’an and Sunnah - Aisyah; Veranika Adelena Melati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to comprehensively understand the concept of shirk in the Quran and Sunnah, exploring its implications for Muslims' beliefs and practices. Through a qualitative approach, this research collects data from various books and journals, analyzing and interpreting them to gain a deeper understanding of shirk. Shirk, as a major sin in Islam, has significant implications for Muslims' faith. The findings of this study reveal that shirk encompasses not only idol worship but also subtle forms of polytheism, such as seeking help from other than Allah and attributing divine attributes to other beings. This research highlights the importance of understanding shirk to maintain the purity of Islamic monotheism and avoid actions that could lead to polytheism. The study provides practical guidance for Muslims to identify and avoid shirk in their daily lives. The novelty of this research lies in its thorough analysis of shirk in the context of the Quran and Sunnah, providing new insights for Muslims to strengthen their faith. This study contributes to a deeper understanding of Islamic monotheism.